Put Some Guts into It: Intestinal Organoid Models to Study Viral Infection - Inés García-Rodríguez; Adithya Sridhar; Dasja Pajkrt; Katja C. Wolthers (Viruses, 2020)
The knowledge about enteric viral infection has vastly increased over the last eight years due to the development of intestinal organoids and enteroids that suppose a step forward from conventional studies using cell lines. Intestinal organoids and enteroids are three-dimensional (3D) models that closely mimic intestinal cellular heterogeneity and organization. The barrier function within these models has been adapted to facilitate viral studies. In this review, several adaptations (such as organoid-derived two-dimensional (2D) monolayers) and original intestinal 3D models are discussed. The specific advantages and applications, as well as improvements of each model are analyzed and an insight into the possible path for the field is given.